Peningkatan Hasil Belajar Matematika Materi Aritmetika Sosial dan Aktivitas Belajar melalui Model Pembelajaran Problem Solving - Supardi, Supardi (Faculty of Teacher Training and Education of Undaris, 2023)
This study aims to: (1) improve the mathematics learning outcomes of Social Arithmetic material;(2) Improving student learning activities through problem solving learning models in class VII A of SMP Negeri 4 Ungaran. Classroom action research was conducted at SMP Negeri 4 Ungaran January-March 2019. Research subjects: 33 grade VII A students. Research results: (1) The application of problem solving learning models can improve mathematics learning outcomes. In the initial learning conditions, the average value was 63.83 with 38.46% learning completeness in the first cycle the average value was 68.59 with 56.41% learning completeness. In the second cycle the average value increased to 84.94 with a learning completeness of 87.18%. The average increase in learning outcomes is 16.35 and an increase in learning completeness is 30.77%. (2) The application of problem solving learning models can increase students' learning activities. Active learning of students in the first cycle 84.62% in the second cycle increased to 92.31%. The increase in student activity is 7.69%.Keywords: Activity, Problem Solving Learning Model